Audio-Visual Aids and the Secondary School Teaching (Global Journal of Human-Social Science, 2014)
In this complex society of today where experiences are innumerable and varied it is not at all possible to present every situation in its original colors hence the opportunities for learning by actual experiences always are not at all possible. It is only through the use of proper audio visual aids that the life situation can be trough in the class room by an enlightened teacher in their simplest form and representing the original to the highest point of similarity which is totally absent in the verbal or lecture method. In the presence of audio aids the attention is attracted interest roused and suitable atmosphere for proper understanding is automatically created, but in the existing traditional method greater efforts are to be made in order to achieve the aforesaid essential requisite. Inspire of the best and sincere efforts on the side of the teacher the net effect as regards under standing or learning in general is quite negligible.
Keywords: audio-visual aids; the secondary school teaching